Comparative analysis of the main medicinal substances and applications of Echium vulgare L. and Echium plantagineum L.: A review. (1st March 2022) - Wang, Wu; Jin, Ju; Xu, Huifeng; Shi, Yanling; Boersch, Mark; Yin, Yuhe
Abstract: Ethnopharmacological relevance: Echium vulgare L. and Echium plantagineum L. originated in the Mediterranean, and were later domesticated in Africa, America, Asia, Europe and Oceania, where they were widely used to treat many diseases including cough, urinary tract infection, fever, inflammation and muscle strain. Aim of the study: The purpose of this review is to provide scientific literature on the traditional uses, bioactive chemical components and pharmacological activities of two species of Echium, and to critically analyze the information provided, so as to understand the current work on these two species and explore the possible prospect of this plant in pharmaceutical research. Methods: Systematic review and meta-analysis were conducted according to Prisma guidelines, and the related literatures searched on Google Academic, Science Direct, Baidu Scholars and China National Knowledge Infrastructure (CNKI) up to June 2021 were reviewed. The key words used are: Echium, E.vulgare, E.plantagineum, plant components, chemical components, pharmacological activities, pharmaceutical products and applications. Thereafter all eligible studies are analyzed and summarized in this review. The selection of manuscripts is based on the following inclusion criteria: the article has years of research or publication, is published in English, Portuguese or Spanish and Chinese, and there are keywords in the title, abstract, keywords or full text of the article. For the selection of manuscripts, first, select articles according to titles, then summarize them, and finally, analyze the full text of the publication. Elimination criteria: 1. Duplicate reports; 2. There are research design defects and poor quality; 3. Incomplete data and unclear ending effect; 4. The statistical method is wrong and cannot be corrected. Results: The pharmacological characteristics of E.vulgare and E.plantagineum can basically support their traditional use, but the medicinal substances contained in them are quite different in composition and content, and the development and application of corresponding products are also different. Conclusions: At present, there is little clinical data about drugs related to the two species, and more research is needed in the future, especially human experiments and clinical trials, to evaluate the cellular and molecular mechanisms based on pharmacological, biological activity and safety studies, and to provide more powerful scientific basis for their traditional medicinal properties. In addition, the further application and development of the medicinal products of E.vulgare and E.plantagineum still need to be precise and identified, so as to give full play to their medicinal potential. Graphical abstract: Image 1 Highlights: Summary of the application of two traditional medicines of Echium . Comparison of two species of Echium to determine plant composition. Medical product applications developed in the past 20 years. Point out the future development trend of Echium industrialization.